Epidemiología de la Leptospirosis en el Departamento del Tolima, Colombia, 2009 – 2011 (2013)
ABSTRACT: To describe the epidemiological behavior of patients with presumptive diagnosis of leptospirosis in the department of Tolima (Colombia), between 2009 and 2011. Methodology: a cross sectional study was conducted, and the epidemiological, clinical, and laboratory findings of 243 patients with presumptive leptospirosis were analyzed using the modified faine criteria. Results: there were 48 cases with positive presumptive diagnosis of leptospirosis (19.8%), 87 negative cases (35.8%), and 108 inconclusive cases (44%). Icterohaemorrhagiae was the most common serovar among presumptively positive patients. Most of the affected patients were male (87%), their mean age was 38 years (sd = 18,4), and they resided in urban areas with poor public services (80.9%). Additionally, hospital treatment was required by 87.6% of the patients, and there were acute cases of the disease (91%), cases with hepatic impairment (65.9%), and a mortality rate of 19%. Conclusions: Leptospirosis is a disease with different demographic and clinical characteristics; moreover, its diagnosis is difficult and sometimes late. Therefore, if an adequate record of some of its features were available, a presumptive diagnosis could be made a priori. Finally, presumptive diagnosis of leptospirosis was associated with outdoor labor, inhabiting places with unsanitary conditions, and having calf pain and fever.